The underpinning of the evaluation of aerobic endurance based on methods established in the late 20th century: A systematic review - Igor Beretić; Dušan Stupar; Romana Romanov (Exercise and Quality of Life)
This systematic review aims to analyze the validity (invasive and noninvasive protocols) of aerobic endurance evaluation methods established in the late 20th century and their practical application in creating training series in different sports events. The PRISMA system was used for systematic review. It was identified that high number of studies support the concept of the evaluation of aerobic endurance, i.e., aerobic threshold (AnT), in terms of its significance for the determination of training series and training intensity aimed at aerobic endurance improvement. During the protocol of testing and construction of the lactate curve (La – work capacity), the method based on sampling and measurement of lactate concentration in blood is given priority as a more valid instrument for AnT determination than the method based on ventilatory parameters and heart frequency. Authors note that the parameters based on which AnT is determined are expressed in different units of measure (m/min, km/h, ml/kg/min) so that AnT, as such, does not only represent the measure of aerobic endurance but also the measure of maximal oxygen consumption (VO2max) and mechanical efficiency. The results of the study indicate that terms related to AnT should be removed from official use. More precisely, researchers and coaches focus on a method related to the interpretation of the lactate curve (at a certain %VO2max) to determine whether there has been an improvement (or not) in aerobic endurance based on its displacement (to the right or to the left).